A comparison of occupant thermal comfort between a green building and a conventional building in the Tropics / Vinod Khanna Nair Kuncheekanna - Vinod Khanna Nair, Kuncheekanna (2013)
This research report conducts a study of comparing the thermal comfort between a green building and a conventional building in tropical climate, namely Malaysia. The green building selected for this study is the Suruhanjaya Tenaga (Energy Commission) headquarters in Putrajaya, also known as the Diamond building. For the conventional building, an electronic manufacturing company called Epson Toyocom Malaysia Sdn. Bhd. was selected. For both the buildings, specific office locations were targeted for data collection area. Field work was conducted within one day in Epson Toyocom Malaysia Sdn. Bhd. (Conventional building) consisting of physical measurements of environmental conditions and thermal survey of its occupants. The Suruhanjaya Tenaga (Green building) physical measurement and thermal survey raw data were provided by Dr.Yau. Both the results were analyzed and compared. 72% of green building occupant voted neutral or thermally satisfied compared to only 51% of conventional building despite the lower operative temperature. In the office in conventional building, the thicker clothing profile and the lack of natural air ventilation may have contributed to this results. Additionally, green building was also voted better acoustically and visually by its occupant compared to conventional building. The design characteristics of the green building compared to the enclosed space in conventional building office is significant in the outcome of the results. It is suggested for organizations to strongly consider sustainable design for future developments.